English Speaking Materials Development Through Describing Picture Method For Junior High Students - holina; Salamun (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research aims to develop the supplementary English material for speaking through describing the Picture. The problem found that the worksheet (LKS) is the dominant book because the amount of coursebook is minimal. The researcher used the Educational Research and Development design. Educational Research and Development is a research design developing educational products, like curriculum, Syllabus, textbooks, instructional media, modules, assessment instruments, etc. The results show that Most students like this book because it is suitable for their needs and supporting them in learning speaking. In conclusion, this product is designed and improved following the learning need and suitability of the product to overcome the problem in education speaking process